Research on Adsorption and Desorption Characteristics of Gas in Coal Rock Based on Nuclear Magnetic Resonance Technology - Xukun Wu; Guangming Zhao; Youlin Xu; Xiangrui Meng; Xiang Cheng (Geofluids)
In order to explore the change characteristics of the adsorption and desorption performance of coal under high gas pressure, low-field nuclear magnetic resonance (LFNMR) technology was used to conduct experimental research on coal adsorption and desorption. The results show that (1) the T2 spectrum distribution diagram shows adsorption peaks (T2=0.01 ms~1 ms) and free peaks (T2=5 ms~1000 ms); (2) with the increase of equilibrium pressure, the peak area of adsorbed methane gradually increased at first and then tended to equilibrium. The initial increase rate of free methane was slower than that of adsorbed methane, and the increase rate of free methane was faster in the later stage; (3) the relationship between the amount of adsorbed gas in the adsorption state of coal and the gas pressure conforms to the Langmuir equation. Taking the equilibrium pressure P=8.7 MPa as the critical hysteresis pressure, it can be divided into two stages which are higher gas pressure (0.5~8.7 MPa) and high gas pressure (8.7~10.33 MPa); the amount of adsorbed gas in the free state has a linear relationship with the gas pressure, and there is no obvious hysteresis; (4) comparative analysis under the same experimental conditions, the mass of the adsorbed gas in the desorption process is greater than the mass of the adsorbed gas in the adsorption process, and there is basically no difference in the mass of the free gas.